O papel do jogo nos processos de aprendizagem de crianças hospitalizadas - Alves, Paula Pereira (2015)
This study sought to understand the role of the game, placing it as a mediating factor in the learning process in children hospitalized in the specific area of the playroom and hospital class, from a look at the childhood and development. To this end, it sought to: analyze the relationship between the game and the educational processes in the hospital class; understand the reasons that lead the child to play during lessons in class hospital; and analyze how the game is in the form of mediating element in the learning processes in the hospital class. The game can be understood as a free activity that allows the child to experience social roles, build concepts about themselves and about the world, develop their personality and understand the culture in which it operates. In a hospital situation in childhood many changes can occur in the child and family routine. Address this issue means remembering that the hospitalized child faces generally varied constraints, due to the exhausting routine or deprivation of children's activities. This research was part of the qualitative research approach model of ethnographic and involved nine children aged between 5 and 11 years admitted to the University Hospital Júlio Muller and attending hospital class and playroom. The methodological tools used were: semi-structured interviews, participant observation and document analysis. The data collection period was six months. From the collected data, we defined two categories of analysis in accordance with relevant themes that emerged in the process. In this work it was observed that the space of the hospital class is much broader than the physical space of the classroom, bounded to carry out educational activities, and the children's learning processes occurring around the hospital space. The toy was shown as a space for learning, leisure and development, being the forerunner game and mediator of various processes among people there attend, favoring the development of linkages, learning rules, the scope of new experiences and facing the illness and hospitalization situations.